PENERAPAN MODEL PROJECT BASED LEARNING TERINTEGRASI ROLE PLAYING UNTUK MENINGKATKAN KARAKTER SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS III SD - Triananda Dewi, Erika; Indawati, Ninik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students character through the implementation of Project Based Learning (PjBL) integrated with Role Playing in Pancasila Education for third-grade elementary school. This research employed Classroom Action Research (CAR) using the Kemmis and Mc Taggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 28 students of grade III at SDN Tanjungrejo 2 Malang. Date were collected through observation and documentation, and analyzed using percentage techniques. The results showed a significant improvement in students character, including, discipline, tolerance, responsibility, and cooperation. In the pre-cycle stage, students character was still in the low to moderate category. After implementing the learning model in cycle I, there was an increase in all indicators into the good category. Further improvement in cycle II, particulary through the use of smaller group formations, resulted in a more significant increase, reaching the very good category in all aspects. These findings indicate that the integration of PjBL and Role Playing, supported by effective group management, can enhance student angagement and develop character holistically. Therefore, this learning model is effective in improving students character in elementary school learning.